URGENSI DESENTRALISASI, DEKONSENTRASI DAN TUGAS PEMBANTUAN DALAM MENJAMIN KEUTUHAN NEGARA KESATUAN REPUBLIK INDONESIA - Mahanani, Anajeng Esri Edhi (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2017)
This article aims to analyze the urgency of decentralization, deconcentration and co-administration as the regional autonomy principle of NKRI. This research is a prescriptive normative research using literature study. The results show that decentralization, deconcentration and co-administration are very important to maintain the integrity of NKRI. These three principles become the bridge of regional independence under the guidance and supervision by the central government, so the government is not centered on one side and on the other side, the region also not